Exploring the Multifaceted Humor Function of Dark Humor in Trevor Noahs Show Son of Patricia - Shabrina, Annisa Nurul; Ain, Qurat ul; Pratama, Hendi (Universitas PGRI Semarang, 2024)
The objective of this study was to gain insight into Trevor Noah's intention for employing dark humor through applying Attardo's humor function framework to his stand-up comedy performance